Music and drama at the Académie royale de musique (Paris), 1774-1789 - Rushton, J; Rushton, Julian (1969)
﻿ Cycles of regeneration and decline in musical drama at the Académie Royale (the Opéra) can be associated with the names of a series of major composers. The first was Lully; 1774 marks the beginning of the "époque de Gluck". Gluck had already attempted the 'reform' of Italian opera in Vienna, with as its chief manifesto the preface (dedication) to Alceste, published in 1769 and translated into French about 1773. It has long been recognized that this reform owed something to the methods of Rameau (which were developed from Lully's). This study therefore opens with a comparison of Rameau and Gluck, showing the fundamental ways in which their methods and intentions differed. The "époche de Gluck" was not a sudden reversal of French operatic method, and one of its features - the introduction of the "international style" (basically Italian) of 18th-century music onto a stage which had generally tended to resist it - had been anticipated in several French operas, mostly mediocre resettings of old libretti but including distinguished works by Gossec and Philidor, composers whose talent Gluck recognized. Consideration of these works is followed by a discussion of the types of aria, recitative, and arioso used in Gluck's French operas, and of Iphigénie en Aulide, the work which definitely established the synthesis of French and Italian elements, and made a return to old French opera impossible while effectively forestalling the attempt to introduce a more purely Italian music. After adapting three of his existing operas, of which Alceste, on a subject also treated by Lully, was the most radically revised, Gluck directly challenged the founder of tragédie-lyrique by resetting Quinault's Armide with comparatively little alteration. Meanwhile various attempts were being made to introduce purely Italian music to France; arrangements of Sacchini were not played at the Opéra, but Piccinni was commissioned to set another, substantially altered, Quinault poem. Roland, J. C. Bach's Amadis, and subsequent resettings by Piccinni, Gossec, and Philidor, are measured in this study against Lully and each other. The controversy between the Gluckistes and Piccinnistes, a literary war in the tradition of the "Guerre des Boufions" raged fiercely from 1777 to the early 1780s. Artistically it came to a head in the two operas of Iphigénie en Tauride which, despite Piccinni's disclaimer of any desire to emulate Gluck, are in many ways comparable and revealing about the two composers' intentions and achievements. Piccinni was brought to Paris as apostle of Italian good taste and the melodic "Période"; but his French operas, far from opposing to Gluck's dramatic conception of opera the purely musical approach that had dominated in Italy for so long, are themseleves thoroughly, indeed strenously dramatic in intention. One consequence of this is that although many composers paid artistic homage to Gluck, the majority of their works resemble more closely those of Piccinni; Gluck was personally inimitable, and in any case belonged to an earlier generation. Moreover a critical study of "Piccinniste" melody suggests that elegance and adherence to the "Période" frequently produced music which, in terms of its own musical development and of the dramatic articulation to which it is supposed to contribute, is superficial; both Piccinni and Sacchini were more successful dramatically in the short forms and ariosi for which French precedent was stronger, than in the Italianate aria and recitativo accompagnato. The operatic genre most typical of the period, and the most successful, was tragédie-lyrique, frequently with Greek or 17th-century French dramas as model. The French composers, however, concentrated on comedy, pastoral, and non-tragic adventure operas. While Gluck's and Piccinni's pastoral operas were relative failures, successful composers of lighter genres, including Floquet and Grétry, were unequal to the challenge of tragedy. The later works of Philidor and Gossec kept the possibility of indigenous French opera alive, particularly as their work shows a closer relation to their own past (the 'chant français') than did their contemporaries'. With many points of interest, these works are uneven in quality; they include such oddities as Candeille's Fizarre, Dezède's "opéra féerie" Alcindor, and the "paysannerie larmoyante" Rosine by Gossec. The direct succession to Gluck was in the work of actual or intended pupils and shows strong symptoms of decadence, and exaggeration of techniques and passions. Lemoyne and Salieri both modified their manner after their first "horror" operas, Electre and Les Danides; the former declared himself Piccinniste but without making any significant change of style. Salieri also approaches Piccinni when less overtly copying Gluck, in his sober Les Horaces and exotic Tarare. Vogel's La Tolson d'Or, dedicated to Gluck, imitates his almost too closely in places, but elsewhere escapes into the (more Piccinnian) language of his own generation. Piccinni's last works met with varying degrees of success or failure; they show intermittently (in Didon and Pénélope) a deepening dramatic insight. His dramatic intentions - which led to the suggestion that he had become a Gluckiste - may have contributed to his eclipse, since the increasingly popular Italian cantibale had found a more consistent champion in Sacchini. The latter's musical gifts to some extent disguised his relative lack of interest in drama, a penchant which permits the discussion of him in this study to be comparatively brief. The last overtly Piccinniste opera was ??'s Antigone (1790), but already a synthesis between the allegedly rival trends was apparent in two adaptations of Metastasio's ?? set by Cherubini and Vogel. The heritage of the ?? may be traced through the differing operatic fashions of Revolution, Empire, and Restoration, in the work of Cherubini and ?? (mainly serious ??) and Spontini, who restored the supremacy of the Opéra under Napoleon. It should be clear that this somewhat nebulous term "Piccinniste", implying an opera which musical fecundity often takes the place of dramatic ?? and a melodramatic energy that of Gluck's characteristic control, fits all these composers better than "Gluckiste". Piccinni however was no leader, and no school should bear his name. The trend he represented was wide-spread and existed even before Gluck reached Paris; a dramatically intended opera with room for musical expansion, a mixture of French continuity and Italian aria forms. Of this trend Gluck was the supreme master; and if he formed no school his far-reaching influence had its basis in the work of several composers working in Paris between 1767 and 1790 who, in wasy befitting their generation and nationality, followed his lead in mingling the techniques and structures of the two previously irreconcilable 18th-century operatic forms.